indonesia Analisa Bentuk Komunikasi Dan Standar Bahasa Inggris SMCP Dalam Dunia Maritim Untuk Menunjang Keselamatan Pelayaran Internasional Di MT. Tonda Source - Arya Nabil Abyan; Supangat; Kuncowati (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
Effective communication and structured language standards are key elements in ensuring the safety of international shipping. This article discusses the process between ships and related parties, such as control vessels, as well as between on the high seas, with a focus on the importance of using STANDARD MARITIME COMMUNICATION PHRASES (SMCP) developed by the INTERNATIONAL MARITIME ORGANIZATION (IMO). SMCP is designed to reduce misunderstandings in emergency and operational situations. This study explores the implementation of SMCP in various scenarios, such as port maneuvers, communication in bad weather, and emergency evacuation, using case studies and simulations. The results of the analysis indicate that obstacles such as cultural differences, accents, and training incompatibilities can affect communication effectiveness. Thus, recommendations are given to improve seafarer training and the integration of modern communication technology to support global shipping safety. The research framework is that all ship operational activities have a very important thing, especially the operation of communication and navigation equipment on board, so it is necessary to conduct an analysis in this study. One effort to improve the understanding of ship watch officers about the operation of communication and navigation equipment above is to conduct routine checks and evaluations of the training. so that the watch officers can understand the importance of safety when sailing on the high seas.